SP18 POCUS: pick the lit. Well and less well studies from the scene. (11th August 2022) - Coppens, Steve; Hoogma, Danny Feike; Dreelinck, Rebekka; Loon, Phillipe Van
Abstract : Introduction: Research regarding Point of care ultrasound (POCUS) has been steadily growing since its introduction in critical care and emergency medicine more than a decade ago. It encompasses a whole array of skills targeting specific organs like the heart, lungs, airway and evaluating a patient's functional status using the ultrasound (US). Exactly these broad applications and myriad of possibilities have made POCUS very intimidating for the novice. It is beyond the scope of this lecture and abstract to focus on all these aspects. Instead, we will try to refresh the general knowledge and give our top picks of POCUS literature, while pointing out a few pitfalls and shortcomings in literature and training. Discussion: General: The most influential POCUS articles for regional anesthesiologists are the two special articles by a joint panel of regional anesthesiologists and pain specialists. 'American Society of Regional Anesthesia (ASRA) and Pain Medicine expert panel recommendations on point-of-care ultrasound education and training for regional anesthesiologists and pain physicians—part I and II' 1, 2 Haskins et al. wrote a series of recommendations after a thorough literature research. What is particularly ingenious in these thoroughly fascinating papers is the links they make to regional anesthesia. Cardiac POCUS immediately becomes more interesting for a locoregional specialist, when it's examined from a local anesthetic toxicity evaluation (LAST) perspective. Or when it's implemented for a decision for a hip fracture spinal after evaluation of aortic valve stenosis. The extensive recommendations, clear images and sheer number of references signifies its importance. Part two focuses on a problem we already previously hinted at. The countless possibilities POCUS offers, makes training and gaining proficiency exceedingly harrowing. The joint ASRA/pain panel tries to define minimum training recommendations and should be considered as the reference when setting up a POCUS skill program anywhere. It is exactly this educational advice which we as authors perceive to be extremely important in this paper. POCUS has been mostly sidetracked by inadequate exposure and failure to implement minimum standards in èresidency. These two excellent publications are a sheer treasure trove of information and should be the top pick of any regional specialist reading list. Specific: The most important general POCUS skill for anesthesiologists will arguably be the evaluation of gastric content and volume. Our top picks here would be 'Validation of a mathematical model for ultrasound assessment of gastric volume by gastroscopic examination' which is a brilliant Randomized Controlled Trial (RCT) refining the idea of calculating gastric fluid volume by Perlas et al. We consider it an invaluable article providing easy to use formulas with practical implications for clinical decision making. The systematic review by Van de Putte et al. published in the British Journal of Anaesthesia: 'Ultrasound assessment of gastric content and volume' is a must read for everybody who wants to excel at this key POCUS skill. 3, 4 It presents a full understanding of the different formulas to calculate volume, while supplying all available evidence in a clear way. POCUS of the airway is a fascinating aspect of the possibilities US offers us. Being able to quickly assess an esophageal intubation with the double track sign might be more helpful for the novice in airway management. However, the possibility to reliably identify the cricothyroid membrane even in morbid obese patients is immensely helpful for anesthesiologists. Kristensen et al. have published quite a few interesting papers regarding this topic. 5, 6 Although lung US scanning might not be the most practiced skill for regional focused anesthesiologists, the ability to quickly assess (with high accuracy) a pneumothorax is invaluable, especially when performing infra and supraclavicular blocks. No Lung POCUS overview would be complete without mentioning the plethora of papers published by Daniel A Lichtenstein. His most influential papers revolved around the implementation of the so-called 'BLUE protocol' and respiratory failure. 7 However it is 'A Bedside Ultrasound Sign Ruling Out Pneumothorax in the Critically III', as one of the first papers detailing lung sliding and analyzing the specificity and sensitivity of the US that really captures our heart. 8 Incredibly this RCT was already published back in 1995 and has more than 500 citations. Finally, a recent study with a catchy title: 'Not so FAST - Chest ultrasound underdiagnoses traumatic pneumothorax' would be our only pick in the less well studies category. 9 It clearly shows the dangers of retrospective, monocenter studies presenting vastly conflicting results. Diagnostic accuracy studies should follow STARD guidelines, while in this publication only patients with confirmed pneumothorax were included in the study, instead of all patients with suspected pneumothorax. 10 Furthermore, the study was performed by radiologists, not familiar with the specifics of trauma pneumothorax identification. They also incorporated it in the Focused assessment with sonography (FAST) exam, using a phased array or curvilinear probe which is not suitable for proper pneumothorax detection. Although there are still many topics in POCUS left, like FAST, eFAST, volume status ascertainment, or even venous access to name but a few, it is well beyond the framework of our small overview to elaborate further. Conclusion: POCUS is here to stay and has become the gold standard as a diagnostic tool in only a few years. Ultrasounds have become ubiquitous, making its routine use feasible. The dazzling number of possible applications can be daunting for the novice, however online training resources are readily available for everyone. Lack of teaching and training in standard curriculum remains a serious stumbling block. References: Haskins SC, Bronshteyn Y, Perlas A, El-Boghdadly K, Zimmerman J, Silva M et al. American Society of Regional Anesthesia and Pain Medicine expert panel recommendations on point-of-care ultrasound education and training for regional anesthesiologists and pain physicians—part I: clinical indications. Regional Anesthesia & Pain Medicine 2021; 46: 1031–1047. Haskins SC, Bronshteyn Y, Perlas A, et al. American Society of Regional Anesthesia and Pain Medicine expert panel recommendations on point-of-care ultrasound education and training for regional anesthesiologists and pain physicians—part II: recommendations. Regional Anesthesia & Pain Medicine 2021; 46 : 1048–1060. Van de Putte P, Perlas A. Ultrasound assessment of gastric content and volume. British Journal of Anaesthesia 2014; 113 : 12–22. Perlas A, Mitsakakis N, Liu L, et al. Validation of a mathematical model for ultrasound assessment of gastric volume by gastroscopic examination. Anesthesia & Analgesia 2013; 116 : 357–363. Kristensen MS, Teoh WHL, Baker PA. Percutaneous emergency airway access; prevention, preparation, technique and training. British Journal of Anaesthesia 2015; 114 : 357–361. Kristensen MS, Teoh WH, Rudolph SS, et al. Structured approach to ultrasound-guided identification of the cricothyroid membrane: a randomized comparison with the palpation method in the morbidly obese. British Journal of Anaesthesia 2015; 114 : 1003–1004. Lichtenstein DA, Mezière GA. Relevance of lung ultrasound in the diagnosis of acute respiratory failure*: the BLUE protocol. Chest 2008; 134 : 117–125. Lichtenstein DA, Menu Y. A Bedside ultrasound sign ruling out pneumothorax in the critically III. Chest 1995; 108 : 1345–1348. Santorelli JE, Chau H, Godat L, et al . Not so FAST—Chest ultrasound underdiagnoses traumatic pneumothorax. Journal of Trauma and Acute Care Surgery 2022; 92 : 44–48. Bossuyt PM, Reitsma JB, Bruns DE, et al. STARD 2015: an updated list of essential items for reporting diagnostic accuracy studies. BMJ 2015; h5527.